Evaluate the above summation for .
Note - You have to use a calculator at the last step of the solution if you generalize it for all .
Bonus - Generalize it for all .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is possible to write the sum in this way:
S ( n ) = i = 0 ∑ ⌊ 2 n − 1 ⌋ ( i n − 1 − i ) n − 2 i 2 n − 1 − 2 i = 2 1 i = 0 ∑ ⌊ 2 n − 1 ⌋ ( i n − 1 − i ) ∫ 0 2 x n − 2 i − 1 d x = 2 1 ∫ 0 2 d x i = 0 ∑ ⌊ 2 n − 1 ⌋ ( i n − 1 − i ) x n − 2 i − 1
Let f ( n ) = i = 0 ∑ ⌊ 2 n − 1 ⌋ ( i n − 1 − i ) x n − 2 i − 1
Using Pascal's identity for binomial coefficient we have
f ( n + 1 ) = i = 0 ∑ ⌊ 2 n ⌋ ( i n − i ) x n − 2 i = i = 0 ∑ ⌊ 2 n − 1 ⌋ ( i n − 1 − i ) x n − 2 i + i = 1 ∑ ⌊ 2 n ⌋ ( i − 1 n − 1 − i ) x n − 2 i
Setting i = k − 1 in f ( n ) and using the property of the floor function we could write the following linear recurrence relation:
f ( n + 1 ) = x f ( n ) + f ( n − 1 )
with f ( 1 ) = 1 and f ( 2 ) = x .
Solving the recurrence relation in the standard way we have:
\[
f(n)= \frac{1}{2^{n}}\frac{1}{(x-\sqrt{x^2+4})^2+4} \left[ 8\left(x+\sqrt{x^2+4}\right)^{n-1}+2\left(x-\sqrt{x^2+4}\right)^{n+1}\right]
\]
Taking the integral we finally have
S ( n ) = 2 n ( 1 + 2 ) n + ( 1 − 2 ) n − 1 + ( − 1 ) n + 1
So:
S ( 2 0 ) = 5 5 6 5 4 8 8 4